Prophylactic Misoprostol-Oxytocin Combination in Preventing Postpartum Hemorrhage : A Meta-Analysis - Rohman, Gilang Rizqy Perdana Aries; Diana, Lani; Sujiati, Tatik (Fakultas Kedokteran Universitas Andalas, 2025)
Background: Postpartum hemorrhage (PPH) remains the leading cause of maternal mortality worldwide. Active management of the third stage of labor, including prophylactic uterotonics, is essential in reducing PPH incidence. Oxytocin is the first-line agent; however, misoprostol has been considered as an adjunct due to its stability, accessibility, and effectiveness. This meta-analysis evaluates the efficacy of the misoprostol-oxytocin combination compared to oxytocin alone in preventing PPH. Methods: A systematic literature search was conducted following PRISMA guidelines using PubMed, ScienceDirect, and Cochrane Library up to November 28, 2024. Randomized controlled trials (RCTs) comparing the misoprostol-oxytocin combination versus oxytocin alone for PPH prevention were included. Statistical analysis was performed using Review Manager 5.4, with mean difference (MD) and relative risk (RR) as effect measures. Heterogeneity was assessed using the I² statistic. Results: A total of seven RCTs met the inclusion criteria. The misoprostol-oxytocin combination significantly reduced the risk of PPH compared to oxytocin alone (RR 0.71; 95% CI 0.55–0.91; p=0.007; I²=54%). Blood loss was significantly lower in the combination group (MD -33.77 mL; 95% CI -62.27 to -5.26; p=0.02; I²=80%). Hemoglobin drop was also reduced (MD -0.75 g/dL; 95% CI -1.48 to -0.01; p=0.02; I²=84%). However, the combination therapy was associated with a higher incidence of pyrexia. Conclusion:The combination of misoprostol and oxytocin is more effective than oxytocin alone in reducing postpartum blood loss and hemoglobin drop. Despite increased pyrexia rates, its benefits in preventing PPH may outweigh the risks, particularly in high-risk populations. Further large-scale studies are needed to refine dosing strategies and assess long-term outcomes.